Study on crack width and crack resistance of eccentrically tensioned steel-reinforced concrete members prestressed by CFRP tendons. (1st February 2022) - Deng, Yu; Gui, Jinyang; Zhang, Hexin; Taliercio, Alberto; Zhang, Peng; Wong, Simon H.F.; Sukontasukkul, Piti; Khan, Afrasyab; Li, Lin; Tang, Yunchao; Chen, Xingyu
Highlights: A very early study on crack resistance of PSRC members under eccentric tension. Using CFRP tendons for prestressing SRC members under eccentric tension. Test data-enhanced analytical method for cracking load estimation. Design formula for estimating the crack resistance. Abstract: In recent decades, steel-reinforced concrete (SRC) members under eccentrical tension have been adopted more frequently in modern buildings due to the constraints of more complex structural design/detailing that accompanying contemporary architectural creations. Crack resistance of this type of structures has become a critical design consideration but received insufficient research attention in the past. In this context, the anti-cracking performance of prestressed SRC columns reinforced with CFRP tendons under eccentric tensile loads is investigated experimentally and analytically with the following first-hand experimental validations: 1) prestressed CFRP tendons can well strengthen SRC columns under eccentric tensile load and restrain the crack propagation; 2) an increase in the load eccentricity progressively weakened the influence of prestressing tension level on the cracking load; 3) specimens with the higher prestressed tension level, larger longitudinal reinforcement diameter, and flange thickness exhibited greater crack resistance capacity. Furthermore, the plane-section assumption was also validated in this study. A test data-enhanced analytical method was proposed for determining the cracking load of PSRC columns.